Timeliness and contract enforceability in intermediate goods trade - Elisa Gamberoni; Rainer Lanz; Roberta Piermartini (World Trade Organization (WTO), 2010)
In particular, the ability to export on time is crucial to explain comparative advantage in intermediate goods. These findings underscore the importance of investing in infrastructure and fostering trade facilitation to boost a country's participation in production networks. Furthermore, we contribute to the so-called distance puzzle by showing that the increasing importance of distance over time is in part driven by trade in intermediate goods.
Keywords: F13; F14; L60; 330; aid for trade; trade facilitation; offshoring; export times; quality of infrastructure; quality of institutions; comparative advantage; Vorprodukt; Außenhandel; Außenhandelsförderung; Offshoring